2022
DOI: 10.1093/psyrad/kkac014
|View full text |Cite
|
Sign up to set email alerts
|

Neural correlations between cognitive deficits and emotion regulation strategies: understanding emotion dysregulation in depression from the perspective of cognitive control and cognitive biases

Abstract: The link between cognitive function and emotion regulation may be helpful in better understanding the onset, maintenance, and treatment for depression. However, it remains unclear whether there are neural correlates between emotion dysregulation and cognitive deficits in depression. To address this question, we first review the neural representations of emotion dysregulation and cognitive deficits in depression (including deficits in cognitive control and cognitive biases). Based on the comparisons of neural r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 181 publications
(245 reference statements)
0
6
0
Order By: Relevance
“…The ventral striatum, including the nucleus accumbens, is implicated in affective and motivational processing (Delgado, 2007). The insula, along with the striatum, is implicated in the regulation of emotions and subjective emotional states (Chen et al, 2018; Wei et al, 2022). Our findings further illustrate that the AI, along with the striatum, is involved in the integration of sensory, interoceptive, and emotional information to create a conscious evaluation of affective reactivity (Nanda et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The ventral striatum, including the nucleus accumbens, is implicated in affective and motivational processing (Delgado, 2007). The insula, along with the striatum, is implicated in the regulation of emotions and subjective emotional states (Chen et al, 2018; Wei et al, 2022). Our findings further illustrate that the AI, along with the striatum, is involved in the integration of sensory, interoceptive, and emotional information to create a conscious evaluation of affective reactivity (Nanda et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…However, despite researchers linking high emotional inertia to inappropriate use of dampening (i.e., emotion dysregulation), it is unclear whether this resistance to altered emotional states is a proactive or reactive process. Recent studies have pointed out that emotion dysregulation is related to cognitive bias, which suggests a need to examine the nature of high emotional inertia ( Gao, Yan & Yuan, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…This implies that the worse the sleep quality, the more serious the depressive and anxiety symptoms. Sleep is thought to play a critical role in brain development and function ( 34 36 ), and insomnia can lead to cognitive decline and a range of physical symptoms ( 37 , 38 ), and cognitive control is present throughout the emotional regulation process ( 39 ). In the current research, adolescents with MDD with high insomnia showed more severe depression, more physical symptoms, reduced cognitive function, and feelings of hopelessness.…”
Section: Discussionmentioning
confidence: 99%